Pro Spring 2.5 - Chakraborty, Anirvan; Ditt, Jessica; Vukotic, Aleksa; Machacek, Jan (Apress : Imprint: Apress, 2008)
The move from so-called heavyweight architectures, such as Enterprise JavaBeans, toward lightweight frameworks, like Spring, has not stopped since Pro Spring was published by Rob Harrop and Jan Machacek in 2005; in fact, it's picked up pace. The Spring Framework remains the leader in this move and provides a platform on which you can build your own applications and services. Pro Spring 2.5 covers the new features of Spring 2.5, but moreover, it is focused on the best practices and core standards of contemporary Spring development. As members of the Spring development team at Cake Solutions, the author team brings extensive practical experience gained from working with Spring since version 1.0 and delivering successful systems on top of it. Learn the approaches that really matter in a professional, enterprise-level environment, so you can apply them to your projects today, safe in the knowledge that they just work.